2017
DOI: 10.1080/13506129.2017.1417121
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular longitudinal strain: a tool for diagnosis and prognosis in light-chain amyloidosis

Abstract: FWRVLS should be considered in the diagnostic and prognostic workup in light-chain amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 21 publications
3
14
0
1
Order By: Relevance
“…The present study revealed that a greater LV wall thickness and smaller LV cavity size (measured by both diameter and telediastolic volume) may help to discriminate CA patients from patients with HF and LVH. This data is consistent with results in Uzan et al [6], although in their study controls are formed by patients with LVH without HF. Also, Boldrini et al [21], in a recent article included the LV wall thickness in a diagnostic score of CA in patients with LVH and confirm the diagnostic value of the wall thickness and the LV mass in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that a greater LV wall thickness and smaller LV cavity size (measured by both diameter and telediastolic volume) may help to discriminate CA patients from patients with HF and LVH. This data is consistent with results in Uzan et al [6], although in their study controls are formed by patients with LVH without HF. Also, Boldrini et al [21], in a recent article included the LV wall thickness in a diagnostic score of CA in patients with LVH and confirm the diagnostic value of the wall thickness and the LV mass in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Another echocardiographic study including 105 patients each with AL amyloidosis, hypertrophic cardiomyopathy, and arterial hypertension was conducted to evaluate the diagnostic and prognostic effects of RV function. In that study, the FWS helped distinguish patients with AL amyloidosis from other patients with left ventricular hypertrophy and was also the only independent predictor of mortality after adjustment for Mayo stage and global left ventricular longitudinal strain 9 . Our study showed that all RV systolic function parameters (RVEF, TAPSE, RVFAC, RVLAS, RVGLS, and RVFWS) were significantly associated with prognosis.…”
Section: Discussionsupporting
confidence: 52%
“…In that study, the FWS helped distinguish patients with AL amyloidosis from other patients with left ventricular hypertrophy and was also the only independent predictor of mortality after adjustment for Mayo stage and global left ventricular longitudinal strain. 9 Our study showed that all RV systolic function parameters (RVEF, TAPSE, RVFAC, RVLAS, RVGLS, and RVFWS) were significantly associated with prognosis. This suggests that RV systolic dysfunction is a marker of poor prognosis and that RV assessment should be part of the comprehensive evaluation in patients with AL amyloidosis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Parametry te mają znaczenie rokownicze w amyloidozie AL [28]. Odkształcenie podłużne wolnej ściany prawej komory okazało się jedynym echokardiograficznym predyktorem śmiertelności całkowitej w amyloidozie AL [29]. Wraz z progresją choroby obserwuje się poszerzanie się jamy prawej komory i narastanie niedomykalności trójdzielnej [30].…”
Section: Badanie Echokardiograficzneunclassified